BDNF val66met polymorphism is associated with modified experience-dependent plasticity in human motor cortex - Kleim, Jeffrey A; Chan, Sheila; Pringle, Erin; Schallert, Kellan; Procaccio, Vincent; Jimenez, Richard; Cramer, Steven C (Nature neuroscience, 2006)
Motor training can induce profound physiological plasticity within primary motor cortex, including changes in corticospinal output and motor map topography. Using transcranial magnetic stimulation, we show that training-dependent increases in the amplitude of motor-evoked potentials and motor map reorganization are reduced in healthy subjects with a val66met polymorphism in the brain-derived neurotrophic factor gene ( BDNF ), as compared to subjects without the polymorphism. The results suggest that BDNF is involved in mediating experience-dependent plasticity of human motor cortex.